Habermas and Giddens on praxis and modernity : a constructive comparison - Browne, Craig (Key issues in modern sociology., 2017)
This major new contribution forms a constructive comparison of the social theories of Jürgen Habermas and Anthony Giddens that focuses on their approaches to modernity, their endeavours to develop new perspectives, and their critical rethinking of the modernist vision of an autonomous society.